2013
DOI: 10.1890/es12-00411.1
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term insect herbivory slows soil development in an arid ecosystem

Abstract: Abstract. Although herbivores are well known to alter litter inputs and soil nutrient fluxes, their longterm influences on soil development are largely unknown because of the difficulty of detecting and attributing changes in carbon and nutrient pools against large background levels. The early phase of primary succession reduces this signal-to-noise problem, particularly in arid systems where individual plants can form islands of fertility. We used natural variation in tree-resistance to herbivory, and a 15 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…However, studies investigating the ecological importance of genetic variation in plants and herbivores provide compelling evidence that contemporary evolution as a result of plant–herbivore interactions can have ecosystem‐level effects (Figure : ecosystem engineering side of FB2 ). For example, Classen, Chapman, Whitham, Hart, and Koch (), Classen, Chapman, Whitham, Hart, and Koch () demonstrated that piñon pine ( Pinus edulis ) susceptibility to a scale insect herbivore is correlated with plant traits that increased nitrogen (N) cycling through litter decomposition but reduced N and carbon (C) accumulation in soil over decades. Additionally, selective consumption of particular plants (e.g.…”
Section: Evidence Of Eco‐evolutionary Feedbacks Across Terrestrial Anmentioning
confidence: 99%
“…However, studies investigating the ecological importance of genetic variation in plants and herbivores provide compelling evidence that contemporary evolution as a result of plant–herbivore interactions can have ecosystem‐level effects (Figure : ecosystem engineering side of FB2 ). For example, Classen, Chapman, Whitham, Hart, and Koch (), Classen, Chapman, Whitham, Hart, and Koch () demonstrated that piñon pine ( Pinus edulis ) susceptibility to a scale insect herbivore is correlated with plant traits that increased nitrogen (N) cycling through litter decomposition but reduced N and carbon (C) accumulation in soil over decades. Additionally, selective consumption of particular plants (e.g.…”
Section: Evidence Of Eco‐evolutionary Feedbacks Across Terrestrial Anmentioning
confidence: 99%
“…3). The presence of insect herbivores could directly or indirectly alter the amount of labile C and N entering the soil environment (Classen et al 2013) and the composition of decomposer communities (Classen et al 2006). Insect herbivores, in addition to the genotypic composition of the resident plant population, could contribute in a nonadditive fashion to produce the interactive effect of insect herbivores and genotypic composition on N cycling.…”
Section: The Relative Importance Of Multiple Factors Affecting Ecosysmentioning
confidence: 99%
“…For example, in a 2 year study Classen et al (2013) initially found that herbivory on insect resistant and susceptible tree genotypes did not affect litterfall-C inputs and soil C-efflux rates. However, when the study was expanded over 36-54 years, herbivory on susceptible trees was shown to slow soil C and N accumulation by 111 % and 96 %, respectively relative to resistant trees.…”
Section: Conclusion Hypotheses and Research Approachesmentioning
confidence: 99%